Seasonal trophic ecology of the dominant Antarctic coral Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Rossi, S.; Fuentes, Verónica Lorena; Alurralde, Roque Gastón; Lagger, Cristian Fabian; Sahade, Ricardo Jose (Marine Environmental Research)
Antarctic ecosystems present highly marked seasonal patterns in energy input, which in turn determines the biology and ecology of marine invertebrate species. This relationship is stronger at lower levels of the food web, while upper levels may be less dependent on primary production pulses. The pennatulid Malacobelemnon daytoni, is one of the most abundant species in Potter Cove, Antarctica. In order to assess its trophic ecology and energetic strategies, its biochemical (carbohydrates, proteins and lipids), Fatty Acid (FA) and Stable Isotope (SI) (δ15N and δ13C) compositions were studied over a year-round period. The FA and SI profiles suggest an omnivorous diet and opportunistic feeding strategy for the species. These results, together with biochemical analysis (higher lipid and carbohydrate concentration observed in July and October 2009), support the hypothesis that resuspension events may be an important source of energy, reducing the seasonality of food depletion periods in winter. The evidence presented here gives us a better insight into the success that this species has in Potter Cove and under the current environmental changes experienced by the Antarctic Peninsula. Fil: Servetto, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Rossi, S. Universitat Autònoma de Barcelona; España Fil: Fuentes, Verónica Lorena. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias del Mar; España. Universidad de Buenos Aires. Facultad de Cs.exactas y Naturales. Departamento de Biodiversidad y Biología Experimental. Cátedra de Introducción A la Zoologia; Argentina Fil: Alurralde, Roque Gastón. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. ...